1986
DOI: 10.1152/jappl.1986.60.4.1435
|View full text |Cite
|
Sign up to set email alerts
|

Chronic swimming reverses cardiac dysfunction and myosin abnormalities in hypertensive rats

Abstract: The purpose of this study was to determine whether a chronic swimming program could reverse the decreased cardiac function and altered myosin biochemistry found in hearts of rats with established renal hypertension. Ten wk after the onset of hypertension [midpoint (m)], hearts from normotensive controls (C) and hypertensives (H) were studied in an isolated working heart apparatus, and myosin biochemistry was analyzed. Half of the control and hypertensive animals were then subjected to a 10-wk swimming program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…Our findings give support to the improvement of left ventricular performance demonstrated in exercised SHR isolated heart (5,17,19). Although we did not measure cardiac function in the present study, the morphological and mechanical cellular adaptations reported here may contribute to our understanding of the mechanisms underlying the benefits of exercise training on the cardiac function of SHR (i.e., improved left ventricular performance).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings give support to the improvement of left ventricular performance demonstrated in exercised SHR isolated heart (5,17,19). Although we did not measure cardiac function in the present study, the morphological and mechanical cellular adaptations reported here may contribute to our understanding of the mechanisms underlying the benefits of exercise training on the cardiac function of SHR (i.e., improved left ventricular performance).…”
Section: Discussionsupporting
confidence: 79%
“…Although we did not test these mechanisms, the increase in the expression of calciumregulatory proteins such as sarcoplasmic reticulum ATPase, phospholamban and ryanodine receptors in response to exercise training has been reported in hypertensive rat cardiac muscle (17,18). Exercise training has also been shown to induce a shift in ventricular isomyosin towards V1 (higher ATPase and contractile activity compared to V3 isomyosin) in hypertensive rats (19). The effects of exercise training on the action potential waveform and duration of left ventricular myocytes in hypertensive rats remain to be investigated.…”
Section: Discussionmentioning
confidence: 75%
“…Seminal work also has shown that exercise training potentiates LV hypertrophy in hypertension. 33,34 The present results show that baseline inotropy and abundance of both LTCC and NCX were increased in SHR relative to WKY. The present data support experiments showing that SHR hearts with compensatory hypertrophy have enhanced contractility 4 …”
Section: Discussionsupporting
confidence: 50%
“…Tour de France cyclists, triathletes, racing greyhound and whippets, and sled dogs) possess eccentric physiological hypertrophy that is remarkably similar to that of Mstn K/K mice. This often includes reduced EF and FS in resting hearts (Rippe et al 1982, Pape et al 1984, Schaible et al 1986, Colan 1992, Snyder et al 1995, Lonsdale et al 1998, Stepien et al 1998, Whyte et al 2000, Bavegems et al 2005, 2007. Reductions in these parameters are not necessarily pathological as cardiac output is normal in all these subjects including Mstn K/K mice.…”
Section: Aging Mice Young Adultsmentioning
confidence: 99%